Between Territories and Borders - Modenesi, Thiago Vasconcellos; Braga Junior, Amaro Xavier (9 Arte (São Paulo), 2019)
The work is built around an essay on the use of comics in the debate of historical notions about the conflicts between the US and Mexico, the installation of the republic in Mexico, and geographic: with the perception of notions of limit, territory and frontier . It emphasizes how the geographical notions are built around a debate between nature and social behavior, historically constructed. Based on two albums of the character Lieutenant Blueberry of the French comics. Methodologically applies content analysis and hermeneutical critique to associate images and concepts. He concludes by suggesting that by way of the reading exercise and historical setting of these HQs can become an important ally in the hands of teachers who are interested in developing knowledge and skills of both geographical and historical aspects in their students.